A meta-analysis of the effect and safety of platinum-based neoadjuvant chemotherapy in treatment of resectable triple-negative breast cancer. Issue 1 (January 2022) - Feng, Wuna; He, Yujing; Xu, Jingsi; Zhang, Hongya; Si, Yuexiu; Xu, Jiaxuan; Li, Shengzhou
Abstract : Triple-negative breast cancer (TNBC) is the most aggressive and fatal subtype of breast cancer. The effectiveness of platinum-based neoadjuvant chemotherapy in treatment of cancer has many divergent opinions. A search was conducted in the PubMed, EBSCO, Web of Science and Cochrane Library databases for relevant studies published before August 2020. The primary endpoint was pathological complete response (pCR) while the secondary endpoints were objective response rate (ORR), overall survival (OS) and progression-free survival (PFS). Nine randomized controlled trials comprised of 1873 patients were included in this meta-analysis. Platinum-based neoadjuvant chemotherapy showed significant improvements in pCR (RR = 1.51, 95% CI, 1.25–1.82, P < 0.001), ORR (RR = 1.20, 95% CI, 1.07–1.34, P = 0.001), OS (HR=0.56; 95% CI, 0.15–0.96, P < 0.001) and PFS (HR = 0.48, 95% CI, 0.22–0.73, P < 0.001) compared to nonplatinum neoadjuvant chemotherapy. Moreover, addition of platinum compounds did not significantly increase the side effects of any grade. However, there was an increase in blood toxicity of grade 3 patients which meant that it was mainly confined to the bone marrow/blood system. Platinum-based neoadjuvant chemotherapy can safely improve short-term and long-term outcomes in resectable TNBC patients. Abstract : Supplemental Digital Content is available in the text.